Piotr Lenartowicz’s Philosophy and Mathematical Science - Janusz, Robert (Studia Ecologiae et Bioethicae, 2019)
This article discusses Piotr Lenartowicz’s S.J., philosophy of nature in the context of mathematical natural sciences. Lenartowicz based his philosophical reflections on biology on the thinking of Aristotle and not on Galileo’s assumption that mathematics is the language of nature. On the basis of modern physics, which has refuted mechanicism and materialism in quantum mechanics, biology develops, but its philosophy can be still interpreted materialistically. Lenartowicz’s intention was to repair the philosophy of biology by returning to Aristotle. However, it ignores the aspects that mathematical physics has overcome, aspects which have not yet been assimilated by the philosophy of biology.